Hemoglobin mediates the link between the ‘weekend warrior’ physical activity pattern and diabetic retinopathy - Baohua Li; Bobiao Ning; Xinyue Hou; Yipeng Shi; Zefeng Kang (Scientific Reports)
Abstract Diabetic retinopathy (DR), the leading cause of vision loss in elderly individuals, coupled with limited treatment options, has prompted efforts to identify modifiable risk factors associated with DR. The purpose of this study was to explore the associations between the “weekend warrior” (WW) physical activity (PA) pattern and DR risk in U.S. adults and to examine how Hb levels mediate this relationship. Cross-sectional study data were obtained from nationally representative NHANES data from 2007 to 2018. The PA pattern was categorized as inactive, insufficiently active, WW, or regularly active (RA). The study ultimately included 6145 U.S. adults, including 1043 participants with DR and 5102 participants with DM but not DR. Multivariate logistic regression modelling indicated that both the WW (OR = 0.631, 95% CI = 0.487–0.818, P < 0.001) and RA (OR = 0.738, 95% CI = 0.574–0.959, P = 0.018) PA patterns were significant protective factors against DR compared with the inactive PA pattern. Moreover, compared to the RA and insufficiently active PA patterns, WW did not show a significant association with DR, whereas the inactive PA pattern (OR = 1.355, 95% CI = 1.054–1.742, P = 0.018) was a risk factor. Mediation analysis revealed a significant partial mediation effect of Hb level on the association between PA pattern and DR risk, with a mediation ratio of 5.95%. Our study revealed that the WW and RA PA patterns are protective factors against DR and that Hb levels mediate this association. In comparison, the WW PA pattern is the most cost effective for DR prevention.